HUBUNGAN KONSUMSI NATRIUM, MAGNESIUM, KALIUM, KAFEIN, KEBIASAAN MEROKOK DAN AKTIVITAS FISIK DENGAN HIPERTENSI PADA LANSIA (Studi di Desa Wilayah Kerja Puskesmas Duren Kabupaten Semarang Tahun 2017) - Dewi Kurniasih; Dina Rahayuning Pangestuti; Ronny Aruben (Jurnal Kesehatan Masyarakat (Undip), 2017)
Hypertension still the main causes of coronary heart disease and stroke. The risk of hypertension is more bigger when getting old. The other controlled factors are dietary pattern, life style, physical activity, obesity and stress. The research purpose was to analyze the correlation of dietaries (sodium, magnesium, potassium micronutrients and caffeine) and life style (smoking and physical activity) with hypertension in elderly. This research type was descriptive observational study with cross sectional approach. The purposive proportional sampling technique was used in five villages of Puskesmas Duren duty region with total sample are 40 elderlies. Data were obtained through questionnaires, IPAQ, SM-FFQ with supported by Food Weighing of 15 respondents. Data were analyzed by univariate and bivariate analysis. The result showed that the average of respondent blood pressure was in prehypertension category. Respondents were often consume high potassium (52,5%) than sodium (47,5%) and magnesium (45%). Micronutrients intake of magnesium (35%), sodium and potassium (100%) were low rate. Respondents were often drinking tea (82,5%) than coffee (25%). Most respondents were not smoking (90%) with their physical activities was minimally active (70%). The result showed that there were no significant correlation (p>0,05) between the habit and intake of high sodium, magnesium, potassium, drinking coffee, drinking tea, smoking and physical activity. Elderly more often consume high potassium than sodium and magnesium although all micronutrition was low intake. Elderly more often drinking tea than coffee and smoking. Most respondents still do minimally active in daily life although they had entered into old age stage.